Somnambulism and Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Neurologists in the EEG laboratory of the Hôpital d'Enfants, Dijon, France, have continued their interests and research concerning the association of somnambulism and migraine in childhood.